The current state of supply of micronutrients to food products of Ukrainians - Andrusyshyna, Iryna; Holub , Inna; Lampeka, Olena (Problems of Environmental Biotechnology, 2021)
The real amount of essential and toxic elements in different types of food products is estimated. Content of chemical elements in 220 samples of different types of food products was determined by the method of optical emission spectroscopy with inductively coupled plasma.